(untitled) (Research, Society and Development, 2021)
Home care is a new and expanding practice in dentistry and has been growing even more in the pandemic scenario. In addition to patients who cannot or cannot go to a dental office, healthy people without comorbidities have sought this type of care as a way to avoid contamination by SARS-CoV- . The objectives of this paper are to discuss the biosafety guideline of a home dental care service in Natal/RN, in times of the COVID-19 pandemic, and address biosafety practices before leaving the office for care that must be performed, aiming at the best way to minimize and/or extinguish contamination risks. For this, a narrative literature review was carried out based on the discussion of this guideline, using the descriptors "Home visit", "Dental care" and "COVID-19", for articles in Portuguese and English, between 2016 and 2021. COVID -19 brought a new perspective on biosafety care in Home Dentistry, hence the need to follow specific care recommendations. It was concluded that: the guidelines proposed by the Potiguar company optimize and make the AOD more practical and safe; each service must adapt the suggestions made, according to its target audience and the reality of the region; and the guidelines for the moments prior to the beginning of the service itself are related to a good anamnesis and the organization of equipment and supplies needed for each visit. In addition, it is suggested to discuss the subsequent steps of these guidelines as well as proposals for other dental homecare services.